2012
DOI: 10.1039/c2jm33091a
|View full text |Cite
|
Sign up to set email alerts
|

Novel porous carbon materials with ultrahigh nitrogen contents for selective CO2 capture

Abstract: Nitrogen-doped carbon materials were prepared by a nanocasting route using tri-continuous mesoporous silica IBN-9 as a hard template. Rationally choosing carbon precursors and carefully controlling activation conditions result in an optimized material denoted as IBN9-NC1-A, which possesses a very high nitrogen doping concentration ($13 wt%) and a large surface area of 890 m 2 g À1 arising from micropores (<1 nm). It exhibits an excellent performance for CO 2 adsorption over a wide range of CO 2 pressures. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 48 publications
6
131
3
Order By: Relevance
“…This is confirmed by the increasing number of papers published in recent years [4][5][6][9][10][11][12][13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 55%
“…This is confirmed by the increasing number of papers published in recent years [4][5][6][9][10][11][12][13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 55%
“…Following this strategy, Han et al developed porous carbon materials by using a tri-continuous mesoporous silica IBN-9 as a hard template, the resulted samples after KOH activation exhibited very high CO 2 uptakes of 19.8 and 46.3 wt. % at 1 and 8 bar, respectively (25°C) (Zhao et al, 2012a). Similar results by using other templates and carbon precursors are reported by a number of groups (Pevida et al, 2008;Li et al, 2010;Xia et al, 2011;Wang and Yang, 2012).…”
Section: Nitrogen-modified Carbonssupporting
confidence: 73%
“…The GO materials were synthesized from natural graphite powder using either the classical Hummer's method [14] (hereafter, HGO) or an improved Hummer's method [27] (hereafter, IGO). The detailed GO synthesis procedures are presented in reference [25] and in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Besides having minimal production costs, they are structurally stable in a wide range of temperatures and can be functionalized with diverse types of chemical groups. This allows one to tailor their selectivity towards specific gases such as CO 2 [14,15]. Analogously, for nanostructured carbon materials, it has been found that the presence of functional groups containing oxygen favors CO 2 uptake [16].…”
Section: Introductionmentioning
confidence: 99%